Gasification of pyrolysis chars from sewage sludge. (1st March 2015) - Nowicki, Lech; Markowski, Maciej
Highlights: TG–MS study of the gasification of sewage sludge chars was performed. Three reaction rate models for gas–solid reaction with CO2 and H2 O were identified. The original quasi-quantitative analysis of TG–MS data was proposed. Abstract: Gasification of char derived from sewage sludge was studied by using the TG–MS system. Experiments were carried out at different temperatures and steam concentrations. The temperatures of 700–900 °C were necessary to complete the conversion in reasonable time. Three reaction rate models for gas–solid reaction were applied to describe the effect of char conversion on the reaction rate. In comparison to the shrinking core model for reaction-controlled regime and random pore distribution models, simple pseudo-homogeneous first-order kinetics was found to be the best for predicting the rate of char steam gasification. Kinetic parameters estimated from the experimental data are in accordance with the literature for lignocellulosic char gasification and are the first ones published for sewage sludge char gasification.